Juridical Review of Social Media Defamation - Okta Lestari Br. Ginting; Abdul Razak Nasution; Saiful Azmi Hasibuan (CERED Indonesia Institute, 2022)
In the Civil Code, the existence of the issue of provisions on Defamation is grouped in the Third Book of Perikatan Chapter II Perikatan which was born for the benefit of the Law. In general, insults in the Civil Code are classified as a genus of Unlawful Acts as regulated in Article 1365 of the Civil Code, where the provisions of contempt are specifically regulated in Articles 1372 to 1380 of the Civil Code. Where in this study is a defamation problem to find out the juridical review of damages on social media based on civil law. The claim for damages aims to regain the honor of defamation. The fundamental difference between the prohibition of defamation in criminal law and civil law lies in the purpose and purpose of the sanction. In criminal law, it lies in the institution of criminal sanctions that are believed to have inhibition power, while in civil law it means the fulfillment of compensation due to defamation.